Sales Forecasting Application Using The Triple Exponential Smoothing Method Based on Android - Ichsan, Muhammad Ichsan; Samsudin; Muliani Harahap, Aninda (Journal of Information Systems and Technology Research, 2023)
Forecasting is the art and science of predicting future events. This can be done by involving taking past data and placing it into the future with a form of mathematical model. The application of the Triple Exponential Smoothing Method is very appropriate to solve the above problems because the Triple Exponential Smoothing Method is used in short-term forecasting, usually only 1 month ahead. The Triple Exponential Smoothing method assumes that the data fluctuates around a fixed mean value, without an even trend or growth pattern. the author conducted research related to the calculation of the development of laptop purchases at CV.Gaharu.Com problems often occur, especially the problem of calculating laptop sales predictions such as the absence of a special system in calculating laptop sales in the coming period so that the company's stock often runs low and is not proportional to consumer demand which is growing rapidly and increasing, as well as in making laptop sales reports are still processed with a fairly simple application so that the reports obtained are less accurate. The research method used by the author is using the R&D (Research and Development) research method. The method of data collection was carried out in this study, namely by means of observation, interviews, and literature study. The steps taken are database design and describe the workflow of the application to be built using UML. At this stage the author designs the interface to produce an interface that is in accordance with the functions required for the application to be built. The system development method used by the researcher is the waterfall.